New species of Leptocaris and a new record of Darcythompsonia inopinata (Harpacticoida: Darcythompsoniidae) from Colombia (2017)
Water samples taken from Rodadero Bay (Colombia) yielded three species of harpacticoid copepods of the family Darcythompsoniidae. Leptocaris colombiana sp. nov. is attributed to the brevicornis-group, and is characterized by the five-segmented antennule, discrete (not fused) female genital somite and third urosomite, six setae on the caudal rami, two setae on the antennal exopod, lack of abexopodal seta on the allobasis of the antenna, mandibular palp reduced to one seta, one inner seta only on the first endopodal segment of leg one and second segment with two apical elements, and by three setae on leg five. Leptocaris vicina sp. nov., is attributed to the mangalis-group, and is similar to L. stromatolicola in the armature formula of leg one to leg four, female leg five with two inner small subequal setae and one outer long element, five-segmented female antennule, antenna with one abexopodal seta on allobasis, antennal exopod reduced to two setae, mandibular palp reduced to one seta, and maxilla with two endites. These two species can be separated by the shape of the anal operculum, by the relative length of the endopodal segments of legs two and three, and by the innermost distal spine of the endopodal segment of the antenna. The record of Darcythompsonia inopinata from northern Colombia represents a continuum along the Caribbean coast of the Pacific dominion, Brazilian subregion.